KECAMATAN BLIMBINGSARI DAN KECAMATAN BANGOREJO DALAM SUDUT PANDANG ILMU TOPONOMI DI WILAYAH KABUPATEN BANYUWANGI - Agus Mursidi; Dhalia Sutopo (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2018)
Banyuwangi Regency has a relatively unique area because it consists of coastalareas, plains and mountains. The population has ethnic diversity namely Osing(indigenous ethnic Banyuwangi), Javanese, Madurese, Bugis and Balinese. Thisis an indication of naming a place that has its own characteristics. Blimbingsarisub-district and Bangorejo sub-district are part of Banyuwangi district whichhas historical origin from the time of the ancestors. The study was conductedwith descriptive methods carried out with the planned research phase is the firstphase of the topology study consisting of 24 sub-districts. Of the 24 sub-districts,2 sub-districts were taken, namely Blimbingsari and Bangorejo Districts. Datacollection was carried out by interviews conducted by 1 researcher accompaniedby 1 survey worker. Information on the results of the interviews is then arrangedin the form of categories and analyzed using the triangulation method.Keywords: Blimbingsari District, Bangorejo District, Toponomi, Banyuwangi